ANALISIS KOMPARATIF PERHITUNGAN PAJAK PENGHASILAN ORANG PRIBADI PASAL 21 BERDASARKAN UU NOMOR 7 TAHUN 2021 DENGAN PP NOMOR 58 TAHUN 2023 PADA KLIEN PT HPA UNTUK PERIODE TRIWULAN I TAHUN 2024 - Sundari, Rima; Noerfauziah, Elly Eka (LAND JOURNAL, 2025)
The regulation governing income tax article 21 is Law No. 7 of 2021 but this regulation has weaknesses in the form of calculations that confuse taxpayers which cause taxpayers to be unwilling to pay their taxes. Therefore, the government issued PP No. 58 of 2023. The purpose of this study is to determine the difference in Income Tax Article 21 using Law No. 7 of 2021 with PP No. 58 of 2023. The research method used in this research is quantitative using secondary data and processed using the SPSS application. The analytical tools used in this study are normality test, homogeneity test and mann-whitney U-test. The results showed that there was no significant difference in tax payable article 21 based on Law No. 7 of 2021 with PP No. 58 of 2023.